A Comparison of an Artificial Intelligence Tool to Fundamental Frequency as an Outcome Measure in People Seeking a More Feminine Voice. (11th May 2021) - Bensoussan, Yael; Park, Christopher; Johns, Michael; Brown, Sarah; Pinto, Jeremy; Chang, Joseph; Courey, Mark
Abstract : Objectives/Hypothesis: An artificial intelligence (AI) tool was developed using audio clips of cis‐male and cis‐female voices based on spectral analysis to assess %probability of a voice being perceived as female (%Prob♀). This program was validated with 92% accuracy in cisgender speakers. The aim of the study was to assess the relationship of f o on %Prob♀ by a validated AI tool in a cohort of trans females who underwent intervention to feminize their voice with behavioral modification and/or surgery. Study Design: Cohort study. Methods: Fundamental frequency ( f o ) from prolonged vowel sounds ( f o /a/) and f o from spontaneous speech ( f o ‐sp) were measured using the Kay Pentax Computerized Speech Lab (Montvale, NJ) in trans females postintervention. The same voice samples were analyzed by the AI tool for %Prob♀. Chi‐square analysis and regression models were performed accepting >50% Prob♀ as female voice. Results: Forty‐two patients were available for analysis after intervention. f o ‐sp post‐treatment was positively correlated with %Prob♀ ( R = 0.645 [ P < .001]). Chi‐square analysis showed a significant association between AI %Prob♀ >50% for the speech samples and f o ‐sp >160 Hz ( P < .01). Sixteen of 42 patients reached an f o ‐sp >160 Hz. Of these, the AI program only perceived nine patients as female (>50 %Prob♀). Conclusion: Patients with f o ‐sp >160 Hz after feminization treatments are not necessarily perceived as having a high probability of being female by a validated AI tool. AI may represent a useful outcome measurement tool for patients undergoing gender affirming voice care. Level of Evidence: 3 Laryngoscope, 131:2567–2571, 2021